IMF Survey, Volume 36 Issue 01. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2007)
IMF opens African technical assistance center; interview with Raghuram Rajan; IMF weighs contingent financing; Latin American growth; Nepal seeks prosperity; link between budget institutions, fiscal outcomes; fuel subsidies; IT in Ireland, India, Israel.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet